Crossreactivity of Antibodies Directed against Cardiolipin, DNA, Endothelial Cells and Blood Platelets - Hasselaar, Paula; Derksen, Ronald H W M; Blokzijl, Laya; Groot, Philip G de (Thrombosis and Haemostasis, 1990)
The interrelationship of antibodies directed against cardiolipin (CL), double stranded DNA (dsDNA), endothelial cells (EC) and blood platelets was investigated. IgG fractions, reactive with these antigens, were isolated from the plasmas from 8 patients with systemic lupus erythematosus and tested for crossreactivity with anionic phospholipids (CL, phosphatidylserine, phos-phatidylinositol), zwitterionic phospholipids (phosphatidyl-ethanolamine, phosphatidylcholine), dsDNA, EC and platelets by enzyme-linked immunosorbent assays and for lupus anticoagulant (LAC) activity with a coagulation assay.Our results demonstrate the frequent occurrence of crossreactivity between antibodies to anionic phospholipids, EC and platelets. Crossreactivities between these antibodies and antibodies to dsDNA or zwitterionic phospholipids are exceptional. LAC activity was found in the anti-CL, anti-EC and anti-platelet fractions of only one patient. These findings support the hypothesis that subpopulations of antibodies directed against negatively charged phospholipids can bind to EC and blood platelets, which may have implications for the pathogenetic potential of antiphospholipid antibodies.